IDENTITAS MUSLIMAH IDEAL DALAM MAJALAH HIJABELLA - Dyah Ayu Mardiana (ILKOM 15 UMY 312, 2015)
*312 The ability of the media in constructing reality in many fields such as politic, economy, social, and even fashion, make the media prone to be misused and tend to lose neutrality. As a muslim-majority country, media in Indonesia often constructs the reality of the Islamic world with all of its development, including the concept of ideal muslimah. The concept of ideal muslimah presented by the media is very diverse and different from each other. Magazine, as one of the media product also often addressing this topic, like Hijabella magazine as one of the most influential magazine with muslimah teenager as its largest reader segmentation.